High burden and seasonal variation of paediatric scabies and pyoderma prevalence in The Gambia: A cross-sectional study - Armitage, Edwin P.; Senghore, Elina; Darboe, Saffiatou; Barry, Momodou; Camara, Janko; Bah, Sulayman; Marks, Michael; Cerami, Carla; Roca, Anna; Antonio, Martin; Turner, Claire E.; de Silva, Thushan I. (PLOS Neglected Tropical Diseases, 2019)
Author summary Scabies is a WHO neglected tropical disease which is common in low- and middle-income countries with tropical climates, which can lead to serious compilations via secondary bacterial infection of skin lesions. Group A streptococcal skin infection is known to cause kidney disease, but may also contribute to rheumatic heart disease. Despite this, little is known about the prevalence of common paediatric skin infections in sub-Saharan Africa, or which bacteria most commonly cause skin infections. We conducted a cross-sectional study of skin infections in The Gambia into the prevalence of scabies, pyoderma and fungal infections in children <5 years. We examined 1441 children and found a scabies, pyoderma and fungal infection prevalence of 15.9%, 17.4% and 9.7% respectively, with significantly increased presence of bacterial skin infections in the rainy season. Over half of bacterial skin infections were found to be positive for group A streptococcus. Our study shows that scabies and pyoderma occur commonly in young children in The Gambia, representing a significant exposure to group A streptococcus at a young age, and that there is a strong seasonal effect on pyoderma, which may have implications for treatment strategies.